Sustainable Entrepreneurship Management and Digitalization: A Green Digital Innovation Radar - Petersen Nicolaj H; Fuerst Sascha; Torkkeli Lasse (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Editorial